The 4Cs learning model in the English Tadris Study Program: How fourth-semester students view it - Nanik Shobikah (Journal of Research on English and Language Learning (J-REaLL), 2023)
This study focuses on the student’s perceptions of the critical thinking, communication, collaboration, and creativity (4Cs) learning model. The aim of this study is to analyze how students perceive the 4Cs learning model. This study used a descriptive qualitative method to describe the students' perception of the 4Cs learning model. The respondents of this study are 58 fourth-semester students of English Tadris Study Program consisting of 15 males and 43 females. The data was collected by using questionnaires and interviews. The data was analyzed using the Likert Scale analysis and the interview was analyzed using data reduction, display data, and conclusion. The trustworthiness used triangulation and member check. The findings revealed that the students strongly agreed that the 4Cs learning model is the 21st-century learning model that helps students to enhance their English skills and prepare them for their future careers and also found that many challenges in the 4Cs learning model implementation such as students’ motivation, student’s confidence, and psychological factors; such as shame, low motivation, and less confidence; the limited access to technology and electricity. From this study, it is suggested to integrate and facilitate the 4Cs learning model in the student’s learning process to enhance the student’s skills: critical thinking, communication, collaboration, and creativity.